Scientific and Technical Manpower Projections. Proceedings of the Seminar Including the Formal Papers (Hot Springs, Virginia, April 16-18, 1974) - National Science Foundation, Washington, DC. National Science Board; National Science Foundation, Washington, DC. National Science Board ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
This report contains the proceedings of a seminar conducted by the Ad Hoc Subcommittee on Manpower of the National Science Board. The major topic of the seminar was the scientific and technical manpower projections of supply and demand, since such projections can serve as a major tool in effecting policy decisions. Six major papers were commissioned for the seminar, each with the following themes: (1) the accuracy of past predictions of scientific and technical manpower; (2) the methodology assumptions used, and limitations employed in projections of scientific and engineering manpower supply and demand; (3) the uses, limitations, and impacts of these projects; (4) methods for enabling students to make career decisions; and (5) possible steps to aid students and others over the long term to evaluate the realizability of their anticipated futures. This volume contains the commissioned papers, panel discussions and summaries, and a complete listing of all participants. (Author/MH)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 (Stock Number 038-000-00262-7, $3.75).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Employment Patterns; Labor Economics; Labor Market; Labor Needs; Prediction; Research Methodology; Science Careers; Science Education; Scientific Personnel; Seminars; Technical Occupations; National Science Foundation; Collected Works, Proceedings